Orthodonto-prothetics Treatment of Partial Edentation in Early, Joint and Permanent Dentitions - O. Solomon; L. Solomon (Romanian Society of Oral Rehabilitation, 2010)
In this work had been described the orthodonto-prothetics treatment methods in diferent dentitions and devices specific features in early, joint and permanent dentitions which allow us to have more prophylactic measures and oclusion balance stabilisation. New methods and devices elaboration in dento-maxilla maloclusion and relapse of final orthodontic treatment prevention.